McDonaldization of Online Prostitution Through Michat in Islam's Perspective - Nofy Afifah Anggrahini; Muhammad Jacky; Intan Sukma Cahyani (PT Pro Panoramic Solution, 2026)
The shift in prostitution from conventional practices to online platforms has enabled sex workers to connect directly with customers through social media, replacing localization and pimps. One platform frequently associated with this practice is the Michat application. Online prostitution has become increasingly widespread in Indonesia, including Lamongan Regency, where cases involving Michat have been identified. This study aims to analyze the pattern of online prostitution on Michat using McDonaldization Theory and examine it from an Islamic perspective. The study employed the Critical Hacking Analysis (CHA) method, which is suitable for research conducted in virtual environments. Data were collected through observations within the Michat application, including photos, symbols, and coded information, and were analyzed using McDonaldization Theory. The findings reveal a structured pattern of online prostitution, beginning with downloading and installing Michat, creating an account, accessing the nearby users feature, and selecting accounts based on appearance, offered services, and distance. These practices reflect the principles of efficiency and speed emphasized in McDonaldization. From an Islamic perspective, online prostitution is considered a form of adultery (zina), which is strictly prohibited and carries both legal and spiritual consequences. Beyond individual sin, it also threatens moral values, weakens faith, undermines the sanctity of marriage, and may contribute to increasing divorce rates. The study concludes that digital platforms have rationalized prostitution practices while creating significant social and religious challenges in predominantly Muslim communities.